Biological restorations: Option of reincarnation for severely mutilated teeth - Wadhwani, Kulvinder Kaur; Hasija, Mukesh; Meena, Babita; Wadhwa, Deepti; Yadav, Rakesh (European Journal of General Dentistry, 2013)
Objective: Esthetic and functional rehabilitation of severely mutilated fractured central incisors teeth using homogenous biological fragment bonding. Materials and Methods: Freshly extracted maxillary central incisors were treated endodontically and post spaces were prepared. Intra-radicular biological post core were fabricated from the sectioned roots of extracted canines. Cementation of biological post core in prepared space was done after clinical and radiological confirmation. Subsequent esthetic rehabilitation was done using adaptation of biological crown which was prepared from morphologically similar extracted maxillary central incisor. Results: The association between biological crowns and post core offers excellent esthetic, functional, and psychosocial results, which justifies the use of this technique to achieve the morphofunctional recovery of extensively damaged teeth. Conclusion: The biological restorations are an alternative technique for reconstruction of extensively damaged teeth that provides highly functional and esthetic outcomes.
Keywords: Biological post; central incisors; esthetic